Association of vitamin A status with lung function in children and adolescents with cystic fibrosis - Ioanna Loukou; Maria Moustaki; Olympia Sardeli; Marina Plyta; Christina N. Katsagoni; Konstantinos Douros (Wiley, 2021)
ABSTRACT Importance Vitamin A (or retinol) has considerable antioxidative and anti‐inflammatory attributes and it may have protective effects on the respiratory health of patients with cystic fibrosis (CF). This issue, however, remains controversial. Objective The purpose of the present study was to investigate the relationship between serum retinol levels (SRL) and force expiratory volume in 1 second (FEV1) in patients with CF. Methods All patients with pancreatic insufficiency attending the CF Department of "Agia Sofia" Children's Hospital in Athens, Greece, aged 6 to 19 years during the 2012-2016 period, who could perform spirometry effectively, were included in the study. The impact of SRL on FEV1 was examined longitudinally and analyzed with generalized estimating equations. Results The study included 231 patients and 851 SRL measurements were performed. In 25 (3.2%) cases the SRL were below the 5th percentile of reference distribution; none was above the 95th percentile. The analysis showed that SRL was positively correlated with the FEV1 (P < 0.001). Interpretation In this sample of children and adolescents with CF, vitamin A deficiency was rare. Our results suggest a positive relationship between SRL and FEV1.